Uji Antibakteri Ekstrak Etanol Daun Mangga Golek (Mangifera indica L.) terhadap Bakteri Staphylococcus aureus: Antibacterial Test of Ethanol Extract of Golek Mango Leaves (Mangifera indica L.) Against Staphylococcus aureus Bacteria - Yuniarti, Rafita; Rukmana, Siti; Nasution, Haris Munandar; Rani, Zulmai; Fauzi, Ziza Aisyia Putri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Mango golek is among the numerous beneficial plants in the Mangifera genus. Mango leaves have antibacterial, antifungal, antiviral, and antiparasitic properties. The purpose of this research was to determine how effective an ethanol extract of mango golek leaves was against Staphylococcus aureus bacteria and what kind of secondary metabolites were present in the extract. This study employed laboratory experimental methods such as the maceration method with 70% ethanol solvent, phytochemical screening test, and Mango golek leaf extract (Mangifera indica L.) Staphylococcus aureus antimicrobial activity test at various concentrations of 100 mg/day. mL, 70, 50, 30, and 10 mg/mL using the agar diffusion method. Mango golek leaves ethanol extract included alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids, according to the screening results. values of 100 mg/mL and 70 mg/mL were considered high, while values of 50 and 30 mg/mL were considered moderate. Keywords: cMangifera indica L., Staphylococcus aureus Abstrak Salah satu tanaman dari genus Mangifera adalah mangga golek yang memiliki banyak manfaat. Salah satu keuntungan adalah sifat antiparasit, antijamur, antivirus, dan antibakterinya. Tujuan penelitian ini adalah untuk mengetahui seberapa efektif ekstrak daun mangga golek terhadap Bakteri Staphylococcus aureus dan mengidentifikasi metabolit sekundernya. Dalam penelitian ini, menggunakan metode eksperimental yang meliputi uji fitokimia, pembuatan pelarut etanol 70% dari ekstrak daun mangga golek (Mangifera indica L.), dan uji antibakteri Staphylococcus aureus dengan konsentrasi 100, 70, 50, 30, dan 10 mg/mL menggunakan metode difusi agar. Hasil skrining, ekstrak etanol daun mangga golek mengandung alkaloid, flavonoid, saponin, tanin, dan steroid/triterpenoid. Uji antibakteri, ekstrak daun mangga golek memiliki sifat antimikroba Staphylococcus aureus dengan kategori kuat 100 dan 70 mg/mL dan kategori sedang 50 dan 30 mg/mL. Kata Kunci: Antibakteri, Mangifera indica L, Staphylococcus aureus